The partition of India through the lens of historical trauma: Intergenerational effects on immigrant health in the South Asian diaspora - Farah Qureshi; Supriya Misra; Asma Poshni (Elsevier, 2023)
South Asian immigrants constitute the world's largest diaspora, with an estimated 25 million people tracing their ancestry to the Indian subcontinent. While recent studies find disproportionately high rates of cardiometabolic diseases and some mental conditions among South Asian immigrants across diverse settings, most research on the root causes of these disparities was conducted with limited engagement with the historical forces that shape the South Asian diasporic experience. This review contextualizes the health challenges currently facing the South Asian diaspora within their shared history of over four centuries of European colonization that culminated in the Partition of India in 1947. Building on existing historical trauma theory, we propose a novel theoretical model connecting the collective trauma of the Partition with the health of affected immigrant populations, postulating plausible social, economic, psychological, and biological mechanisms that may explain current patterns. Since no research has explored these links directly, we summarize prior work examining trauma-related mental and physical health outcomes among this group, with a particular focus on populations living in Canada, the United Kingdom, and the United States, where the bulk of diasporic research has been conducted. We also theorize how a historical trauma perspective can be integrated into future public health research and practice to better meet the health needs of South Asian immigrants with origins that trace back to affected regions, and discuss opportunities to expand this model to other postcolonial immigrant populations worldwide.